Multiple Factors Determine the Structure of Bacterial Communities Associated With Aedes albopictus Under Artificial Rearing Conditions - Chen, Shi; Zhang, Dongjing; Augustinos, Antonios; Doudoumis, Vangelis; Bel Mokhtar, Naima; Maiga, Hamidou; Tsiamis, George; Bourtzis, Kostas (Frontiers in Microbiology, 2020)
Insect symbionts are major manipulators of host’s behavior. Their effect on parameters such as fecundity, male mating competitiveness, and biological quality in general, can have a major influence on the effectiveness of the sterile insect technique (SIT). SIT is currently being developed and applied against human disease vectors, including Ae. albopictus, as an environment-friendly method of population suppression, therefore there is a renewed interest on both the characterization of gut microbiota and their exploitation in artificial rearing. In the present study, bacterial communities of eggs, larvae, and adults (both males and females) of artificially-reared Ae. albopictus, were characterized using both culture-dependent and culture-independent approaches. Mosquito-associated bacteria corresponding to thirteen and five bacteria genera were isolated from the larval food and the sugar solution (adult food), respectively. The symbiont community of the females was affected by the provision of a blood meal. Pseudomonas and Enterobacter were either introduced or enhanced with the blood meal, whereas Serratia were relatively stable during the adult stage of females. Maintenance of these taxa in female guts is probably related with blood digestion. Gut-associated microbiota of males and females were different, starting early after emergence and continuing in older stages. Our results indicate that eggs contained bacteria from more than fifteen genera including Bacillus, Chryseobacterium, and Escherichia-Shigella, which were also main components of gut microbiota of female adults before and after blood feeding, indicating potential transmission among generations. Our results provided a thorough study of the egg- and gut-associated bacteria of artificially-reared Ae. albopictus, which can be important for further studies using probiotic bacteria to improve the effectiveness of mosquito artificial rearing and SIT applications.